Femtosecond laser surface irradiation of silicon in air: Pulse repetition rate influence on crater features and surface texture. (June 2020) - Allahyari, E.; JJ Nivas, J.; Avallone, G.; Valadan, M.; Singh, M.; Granata, V.; Cirillo, C.; Vecchione, A.; Bruzzese, R.; Altucci, C.; Amoruso, S.
Highlights: The variation of the craters generated by fs laser irradiation with repetition rate is investigated. The influence of the laser pulse repetition rate on removal rate and surface texture on silicon is addressed. Possible effects of plume shielding on crater features and laser surface structuring at high repetition rate is discussed. Abstract: The influence of the pulse repetition rate on laser irradiation of silicon, in air, with femtosecond laser pulses is experimentally investigated in the range 10 Hz – 200 kHz. The features of the produced crater and the laser-induced periodic surface structures generated on its surface are characterized by exploiting surface profilometry and scanning electron microscopy. The experimental characterization evidences an interesting influence of the pulse repetition rate on the crater size qualitatively addressing a progressive reduction of the material removal efficiency at higher repetition rates. Moreover, also the surface structures produced by an irradiation sequence with a fixed number of laser pulses (namely N = 100) shows a clear dependence on the repetition rate. The observed effects are rationalized by considering the possible influence of plume shielding and heat accumulation effects typically observed during laser processing with high repetition rate laser systems.